Decoding the effects of brining time on the sensory quality, physicochemical properties and flavor characteristics of marinated grass carp meat - Lu Zhang; Yaqin Yu; Qinhui Wen; Shi Nie; Yang Hu; Chunming Tan; Zongcai Tu (Food Chemistry: X)
This study aimed to explore the effects of different brining times on the sensory, physicochemical properties, and volatile organic compounds (VOCs) of marinated grass carp (MGC). The results showed that different brining time changed the sensory quality, color and texture. The moisture content increased significantly with the extension of brining time, while the salt content, protein content, thiobarbituric acid reactive substances (TBARS), and total volatile basic‑nitrogen (TVB-N) decreased (p < 0.05). Free amino acids indicated that sweet amino acids significantly decreased, but bitter and umami amino acids increased. E-nose and E-tongue could clearly distinguish different MGC samples, and gas chromatography ion mobility spectrometry (GC-IMS) identified a total of 72 VOCs. Among them, 11 key VOCs were screened based on the variable importance of predicted component value (VIP) and relative odor activity value (ROAV), and they showed a high correlation with MGC quality. This study provides a theoretical foundation for enhancing the quality and improving the flavor of MGC.